Microfluidics-mediated self-template synthesis of anisotropic hollow ellipsoidal mesoporous silica nanomaterials - Nanjing Hao; Yuan Nie; Amogha Tadimety; Andrew B. Closson; John X. J. Zhang (Materials Research Letters, 2017)
Herein, a facile strategy was firstly developed to synthesize ellipsoidal mesoporous silica nanomaterials (MSNs) with well-ordered parallel channels along the short axis. A miniaturized microfluidic device with spiral-shaped channels was then chosen as a straightforward and general platform to produce the corresponding hollow counterparts of MSNs under mild conditions. Such reaction process carried out in a microfluidic system was further demonstrated to be more rapid and efficient than a conventional batch method under equivalent experimental conditions. The evolution of hollow structure can be well tuned by flow rates (i.e. etching time), providing a new paradigm for rational design and engineering of anisotropic nanostructures.